Flipping Everything Upside Down

Algebra Level 2

A = k = 0 1 2 k 3 B = k = 0 1 2 k \large A = \sum_{k=0}^\infty \dfrac1{\sqrt[3]{2^k}} \qquad \qquad B = \sum_{k=0}^\infty \dfrac1{\sqrt{2^k}}

What is the relationship between A A and B B ?

It is impossible to determine A > B A>B A < B A<B A = B A=B

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Sam Bealing
Jul 1, 2016

As k 0 k \geq 0 it follows that 2 k 1 2 k 3 2 k 1 2 k 3 1 2 k 2^k \geq 1 \implies \sqrt[3]{2^k} \leq \sqrt{2^k} \implies \dfrac{1}{ \sqrt[3]{2^k}} \geq \dfrac{1}{\sqrt{2^k}} .

For k > 0 k>0 we have 2 k > 1 2^k >1 and hence the inequality becomes strict so we have each term of A A is greater than the same term in B B .

A > B \boxed{\boxed{A>B}}

Moderator note:

Good approach comparing termwise.

M K
Jun 30, 2016

Hm, there are several issues with your first equation

  • Numerator is missing a a a
  • Denominator is just 1 r 1 - r

Calvin Lin Staff - 4 years, 11 months ago

Log in to reply

Whoops, my bad. Thanks for the correction!

M K - 4 years, 11 months ago

Typo: 1 2 3 > 1 2 \dfrac{1}{\sqrt[3]{2}} > \dfrac{1}{\sqrt{2}}

Hung Woei Neoh - 4 years, 11 months ago
Joe Previdi
Jul 3, 2016

Since since every term which appears in B also appears in A (every time k is a multiple of 3) and there are more terms than just B's terms, A has every term of B plus more, and therefore A is greater.

Jeannine Myer
Jul 3, 2016

If you write out the sum, you see between the terms which are equal you add a bigger number each time with A. Simple.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...